Transport Oligonucleotides—A Novel System for Intracellular Delivery of Antisense Therapeutics - Markov, Oleg V. (Molecules, 2020)
Biological activity of antisense oligonucleotides (asON), especially those with a neutral backbone, is often attenuated by poor cellular accumulation. In the present proof-of-concept study, we propose a novel delivery system for asONs which implies the delivery of modified antisense oligonucleotides by so-called transport oligonucleotides (tON), which are oligodeoxyribonucleotides complementary to asON conjugated with hydrophobic dodecyl moieties. Two types of tONs, bearing at the 5′-end up to three dodecyl residues attached through non-nucleotide inserts (TD series) or anchored directly to internucleotidic phosphate (TP series), were synthesized. tONs with three dodecyl residues efficiently delivered asON to cells without any signs of cytotoxicity and provided a transfection efficacy comparable to that achieved using Lipofectamine 2000. We found that, in the case of tON with three dodecyl residues, some tON/asON duplexes were excreted from the cells within extracellular vesicles at late stages of transfection. We confirmed the high efficacy of the novel and demonstrated that MDR1 mRNA targeted asON delivered by tON with three dodecyl residues significantly reduced the level of P-glycoprotein and increased the sensitivity of KB-8-5 human carcinoma cells to vinblastine. The obtained results demonstrate the efficacy of lipophilic oligonucleotide carriers and shows they are potentially capable of intracellular delivery of any kind of antisense oligonucleotides.